Two Distinct Compound Heterozygous Constellations (R277X/IVS34-1G〉C and R277X/R1511X) in the Thyroglobulin (TG) Gene in Affected Individuals of a Brazilian Kindred with Congenital Goiter and Defective TG Synthesis - Gutnisky, Viviana J. (2004)
In this study, we have extended our initial molecular studies of a nonconsanguineous family with two affected siblings and one of their nephews with congenital goiter, hypothyroidism, and marked impairment of thyroglobulin synthesis. Genomic DNA sequencing revealed that the index patient (affected nephew) was heterozygous for a single base change of a cytosine to a thymine at nucleotide 886 in exon 7 (886C〉T, mother's mutation) in one allele and for a novel guanine to cytosine transversion at position-1 of the splice acceptor site in intron 34 (IVS34-1G〉C, father's mutation) in the other allele. The two affected siblings inherited the 886C〉T mutation from their mother and a previously reported cytosine to thymine transition at nucleotide 4588 in exon 22 from their father (4588C〉T). The 886C〉T and 4588C〉T substitutions resulted in premature stop codons at amino acids 277 (R277X) and 1511 (R1511X), respectively. In vitro transcription analysis showed that the exon 35 is skipped entirely when the IVS34-1G〉C mutation is present, whereas the wild-type allele is correctly spliced. SSCP (exon 7 and 35) and restriction analysis (exon 22) using Taq I indicated that the two affected siblings, the affected nephew, his mother, and his unaffected brother were all heterozygous for the R277X mutation. The two affected siblings, their father, and three unaffected siblings were all heterozygous for the R1511X mutation, whereas the affected nephew and his father were heterozygous for the IVS34-1G〉C mutation. Moreover, in this kindred, we have characterized polymorphisms (insertion/deletion, microsatellite, and single nucleotide polymorphism) located within introns 18 and 29 and exon 44 that are associated with the described mutations. Haplotype analysis with these polymorphic markers in two unrelated Brazilian families (present family studied and previously reported family) harboring the R277X mutation suggests a founder effect for the R277X mutation. In conclusion, the affected individuals of this family are either compound heterozygous for R277X/IVS34-1G〉C or R277X/R1511X. This observation further supports that thyroglobulin gene mutations display significant intraallelic heterogeneity.